2021
DOI: 10.3390/inorganics9100073
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium(V) Complexes with Siderophore Vitamin E-Hydroxylamino-Triazine Ligands

Abstract: Novel vitamin E chelate siderophore derivatives and their VV and FeIII complexes have been synthesised and the chemical and biological properties have been evaluated. In particular, the α- and δ-tocopherol derivatives with bis-methyldroxylamino triazine (α-tocTHMA) and (δ-tocDPA) as well their VV complexes, [V2VO3(α-tocTHMA)2] and [V2IVO3(δ-tocTHMA)2], have been synthesised and characterised by infrared (IR), nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR) and ultra violet-visible (UV-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Recently new classes of vanadium coordination complexes have been reported that are mild radical initiators and should be able to initiate LPO and induce oxidation [ 14 ]. Interestingly, they are not cytotoxic to embryonic mouse fibroblasts (NIH/3T3) [ 14 ], Cal33 cells or HeLa cells.…”
Section: Reactive Oxygen Species and Lipid Peroxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently new classes of vanadium coordination complexes have been reported that are mild radical initiators and should be able to initiate LPO and induce oxidation [ 14 ]. Interestingly, they are not cytotoxic to embryonic mouse fibroblasts (NIH/3T3) [ 14 ], Cal33 cells or HeLa cells.…”
Section: Reactive Oxygen Species and Lipid Peroxidationmentioning
confidence: 99%
“…Recently new classes of vanadium coordination complexes have been reported that are mild radical initiators and should be able to initiate LPO and induce oxidation [ 14 ]. Interestingly, they are not cytotoxic to embryonic mouse fibroblasts (NIH/3T3) [ 14 ], Cal33 cells or HeLa cells. One class of compounds is vitamin E chelate siderophores with a lipid portion and a metal ion, amphiphilic properties and hydrolytic stability [ 15 ].…”
Section: Reactive Oxygen Species and Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium coordination complexes have been the focus of recent work in cell systems (Scalese et al, 2019;Treviño and Diaz, 2020;Loizou et al, 2021, He et al, 2020Biswas et al, 2022;Ferretti and León, 2022;Ribeiro et al, 2022;Semiz, 2022;Althumairy et al, 2020a;Sahu et al, 2022). Our group has shown that bismaltolatodioxovanadium(IV) (BMOV) and polyoxidovanadates are able to initiate signaling by the luteinizing hormone receptor (LHR), a G-protein coupled receptor (GPCR) (Roess et al, 2008;Crans et al, 2011;Winter et al, 2012;Al-Quatati et al, 2013;Althumairy et al, 2020b;Althumairy et al, 2020c;Althumairy et al, 2020d;Samart et al, 2020).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…When evaluating effects of metal complexes on bacterial cells, it is, however, important to consider that these compounds are coordination complexes and many of these compounds do not remain intact during study due to their inherent hydrolytic instability in complex biological media [25][26][27][28][29]. In addition, the effects of the metal complex versus its ligand can be important, particularly in cases where the ligand has potent effects on the cells being studied [28,[30][31][32]. Here, we use a recently identified anticancer compound, a Schiff base vanadium-based catecholate complex (oxidovanadium(IV) complexed to N-(salicylideneaminato)-N -(2-hydroxyethyl)ethane-1,2-diamine 3,5-di-tertbutylcatecholato ligand) [33,34], which was found to be significantly more potent than cisplatin in several cancer lines including glioma multiforme, an aggressive brain cancer (T98g), lung cancer cells (A549), and pancreas cancer cells (PANC-1) [34].…”
Section: Introductionmentioning
confidence: 99%